A jurisprudential study in the ruling on looking at a foreign woman according to Imamia scholars - Khalaf Ali Khalaf saba ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
A research in which the researcher deals with the jurisprudential opinions of the Imami scholars in the ruling on looking at a foreign woman from the Book of Marriage in the jurisprudence of the Jaafari school, in which it is limited to stating the ruling on looking at the face and The palm of the hand, and without pleasure or suspicion; Because looking at other than them is forbidden by the agreement of Muslim scholars, just as looking at them with pleasure or suspicion is forbidden by agreement.